La NIIF 15 ingresos procedentes de contratos con clientes y su incidencia en los estados financieros de las compañías constructoras - Goyes Rizzo, Mercedes Nathali (2021)
The main objective of this investigation entitled “IFRS 15 (INCOME FROM CONTRACTS WITH CLIENTS) and its impact on the Financial Statements of Construction Companies”, was to analyze the incidence when applying IRFS 15 in the Financial Statements on Construction Companies in Guayaquil. The company chosen for this analysis is “CALAPAM S.A.” which previously applied IAS 11 (Revenue and costs related to construction contracts) and only recognized recurring income. As of 2018, the IFRS 15 came into force and provided a comprehensive framework for revenue’s recognition from ordinary activities from contracts with costumers. In “CALAPAM S.A.” the income and profit were recognized as a percentage based on the work progress of a construction project, unlike IFRS 15 which identifies the circumstances in which certain criteria are met for income from ordinary activities to be recognized; the adoption of these changes affected the financial situation of the company........